The Factors Affecting Audit Quality with Auditor’s Experience as Moderating Variable: Faktor-faktor yang Mempengaruhi Kualitas Audit dengan Pengalaman Auditor sebagai Variabel Moderasi - Elyana, Ema; Whetyningtyas, Aprilia; Ayu Susanti, Diah (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this study was to examine and analyze about the effect of independence, due professional care, locus of control and time budget pressure on audit quality with auditor’s experience as moderating variable at Regional Inspectorate of The Pati Residency. This study used convenience sampling technique with sample of 100 respondents from internal auditors. The analysis used Smart PLS 4.0 Software and the result: (1) Independence had positive effect on audit quality. (2) Due professional care had positive effect on audit quality. (3) Locus of control had positive effect on audit quality. (4) Time budget pressure had no effect on audit quality. (5) Auditor’s experience not able to moderate the effect of independence on audit quality. (6) Auditor’s experience not able to moderate the effect of due professional care on audit quality. (7) Auditor’s experience is able to moderate (strengthens) the effect of locus of control on audit quality. (8) Auditor’s experience not able to moderate the effect of time budget pressure on audit quality